2022
DOI: 10.1007/s11135-022-01519-1
|View full text |Cite
|
Sign up to set email alerts
|

Formative-reflective scheme for the assessment of tourism destination competitiveness: an analysis of Italian municipalities

Abstract: In this article, we propose a formative-reflective scheme for the assessment of Tourism Destination Competitiveness (TDC) based on a combined use of Partial Least Squares-Path Modelling (PLS-PM) and the method recently proposed by Fattore, Pelagatti, and Vittadini (FPV). TDC is conceived as a construct reflecting the tourism performance of a destination, and several determinants are considered, including endowed resources, created resources, and supporting factors. The proposed scheme is applied to a case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The aforementioned guidelines are all sub-indicators that drive the human resource readiness of personnel working in wellness tourism establishments or businesses with a responsibility of providing products and services to tourists, which are conditions for the most significant indicator of the competitiveness assessment factor regarding the environment of tourist destinations that promotes the development and improvement of tourist areas or attractions' competitiveness so they have the readiness and the capacity to become wellness tourism destinations that are distinctive and unique efficiently, effectively, and in accordance with the research of Dwyer [59], Fernández et al [31], Grassini et al [63], Mustafa et al [61], Wang et al [36]. It is found that the human resources in such tourist areas or attractions, especially personnel working in wellness tourism establishments or businesses who are experienced in their line of work and can deliver an impressive health promotion service experience for tourists, are a significant indicator of the competitiveness assessment factor regarding the environment that promotes wellness tourism in the destinations.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The aforementioned guidelines are all sub-indicators that drive the human resource readiness of personnel working in wellness tourism establishments or businesses with a responsibility of providing products and services to tourists, which are conditions for the most significant indicator of the competitiveness assessment factor regarding the environment of tourist destinations that promotes the development and improvement of tourist areas or attractions' competitiveness so they have the readiness and the capacity to become wellness tourism destinations that are distinctive and unique efficiently, effectively, and in accordance with the research of Dwyer [59], Fernández et al [31], Grassini et al [63], Mustafa et al [61], Wang et al [36]. It is found that the human resources in such tourist areas or attractions, especially personnel working in wellness tourism establishments or businesses who are experienced in their line of work and can deliver an impressive health promotion service experience for tourists, are a significant indicator of the competitiveness assessment factor regarding the environment that promotes wellness tourism in the destinations.…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, Salinas Fernández et al [31], Flores-Romero et al [60], Grassini et al [63], Kurek et al [33], Mustafa et al [61], Pan et al [46], Tleuberdinova et al [62], Wang et al [36] pointed out that the readiness of infrastructure in tourist areas or attractions that are wellness tourism destinations which supports the development, improvement, or process of change to elevate their competitiveness capacity and be capable of growing into wellness tourism destinations that are distinctive and unique is considered a driver of competitive capacity that help promote tourist destinations' attractiveness and convince wellness tourists to decide to travel to such tourist attractions and areas easier, and Andrades and Dimanche [41], Armenski et al [38], Bilbao-Terol et al [30], Dwyer [59], Flores-Romero et al [60], Indrajaya et al…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…And based on the previous statistical suggestions (e.g. Gefen et al, 2000;Grassini et al, 2023;Rita et al, 2019), when the factor loading of each individual item is no less than 0.5, the CR exceeds 0.70 and the average variance extracted (AVE) exceeds 0.50, the reliability test results are regarded as acceptable in the statistical analysis. As shown in Table 2, the factor loading in this study ranged from 0.685 to 0.881; CR spanned from 0.818 to 0.942; and the AVE ranged from 0.530 to 0.694.…”
Section: Reliability Analysismentioning
confidence: 99%
“…In addition, TRP assessments are always accompanied by methodological difficulties due to the complexity of the subject of evaluation and the diversity in the use of different types of resources. In this regard, there is a wide variety of approaches and assessment methods proper for the analysis of certain types of TRP and of the territory as a whole [18][19][20][21][22][23][24][25].…”
Section: Related Workmentioning
confidence: 99%